2020
DOI: 10.1136/medethics-2019-105979
|View full text |Cite
|
Sign up to set email alerts
|

A discussion on controversies and ethical dilemmas in prostate cancer screening

Abstract: Prostate cancer (PCa) is one of the the most common cancers in men. A blood test called prostate-specific antigen (PSA) has a potential to pick up this cancer very early and is used for screening of this disease. However, screening for prostate cancer is a matter of debate. Level 1 evidence from randomised controlled trials suggests a reduction in cancer-specific mortality from PCa screening. However, there could be an associated impact on quality of life due to a high proportion of overdiagnosis and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…At the turn of the century, a Spanish study evaluating prostate histology at autopsy identified that men from the third decade onwards have neoplastic lesions of the prostate and 33% of the male population in their eighth decade have prostate cancer (2). In addition, prostate cancer is the most commonly diagnosed malignancy in older men (over the age of 65) worldwide, especially in highly developed countries (Australia, New Zealand, Northern and Western Europe, and North America) (3)(4)(5). The high prevalence of the disease can be attributed to the volume of cases identified through prostate specific antigen (PSA) testing, especially in the United States (6).…”
Section: Introductionmentioning
confidence: 99%
“…At the turn of the century, a Spanish study evaluating prostate histology at autopsy identified that men from the third decade onwards have neoplastic lesions of the prostate and 33% of the male population in their eighth decade have prostate cancer (2). In addition, prostate cancer is the most commonly diagnosed malignancy in older men (over the age of 65) worldwide, especially in highly developed countries (Australia, New Zealand, Northern and Western Europe, and North America) (3)(4)(5). The high prevalence of the disease can be attributed to the volume of cases identified through prostate specific antigen (PSA) testing, especially in the United States (6).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the follow-up for prostate cancer patients includes the use of serological tests [20], such as the blood evaluation of Prostate Speci c Antigen (PSA) [20], or imaging analysis by Fluorodeoxyglucose (FDG)-Positron Emission Tomography (PET) [21] or 18 F-choline PET/Computer Tomography [22]. The PSA blood evaluation is a non-invasive test, but its values are in uenced by numerous variables such as systemic in ammation and prostatitis [23]. On the contrary, molecular imaging analysis is very sensitive but more invasive respect to blood tests.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits and harms of population screening for prostate cancer continue to be debated [ 1 , 2 ]. A simple blood test can measure blood levels of prostate specific antigen (PSA), a protein that when raised in the circulation indicates an increased risk of prostate cancer, and warrants further diagnostic investigations.…”
Section: Introductionmentioning
confidence: 99%
“…However, while a European trial demonstrated that screening using repeated PSA testing reduces prostate cancer specific mortality [ 3 ], the UK CAP trial suggested that there is little prostate cancer specific mortality benefit of a single PSA screen after 10 years of follow-up [ 4 ], and overall the weight of evidence does not indicate that any potential mortality benefit outweighs the risks of overdiagnosis of indolent disease and of overtreatment [ 5 ]. Overdiagnosis and, consequently, overtreatment are substantial problems, leading to unnecessary, unpleasant side-effects for some men, and the benefit-harm trade-offs remain under discussion [ 2 ]. Screening men over 70 is identified by multiple bodies as a low-value activity for a variety of rationales including lack of clinical and economic value [ 6 ].…”
Section: Introductionmentioning
confidence: 99%